2018
DOI: 10.3389/fonc.2018.00107
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Metabolism and Other Targeted Drugs; Potential Impact on Immunotherapy

Abstract: The role of platelets in cancer progression has been well recognized in the field of cancer biology. Emerging studies are elaborating further the additional roles and added extent that platelets play in promoting tumorigenesis. Platelets release factors that support tumor growth and also form heterotypic aggregates with tumor cells, which can provide an immune-evasive advantage. Their most critical role may be the inhibition of immune cell function that can negatively impact the body’s ability in preventing tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 158 publications
(109 reference statements)
0
27
0
Order By: Relevance
“…Platelet remarkable reactivity justifies their involvement in coagulative dysfunctions and thrombotic disorders [5] . Recent evidence supports the notion that platelets can also play a pivotal role in cancer progression, promoting tumorigenesis through factor secretion and metastasis to form immune-evasive aggregates with tumour cells [6] . Platelet dysfunction appears involved in complications of type II diabetes mellitus (DM): hyperglycemia would increase platelet mitochondrial ATP content [7] , but it was also shown that platelet oxidative phosphorylation (OXPHOS) was impaired in type II DM [8] .…”
Section: Platelet Formation and Functionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Platelet remarkable reactivity justifies their involvement in coagulative dysfunctions and thrombotic disorders [5] . Recent evidence supports the notion that platelets can also play a pivotal role in cancer progression, promoting tumorigenesis through factor secretion and metastasis to form immune-evasive aggregates with tumour cells [6] . Platelet dysfunction appears involved in complications of type II diabetes mellitus (DM): hyperglycemia would increase platelet mitochondrial ATP content [7] , but it was also shown that platelet oxidative phosphorylation (OXPHOS) was impaired in type II DM [8] .…”
Section: Platelet Formation and Functionsmentioning
confidence: 72%
“…The rapid response rate of platelet activation involves dramatic shape changes, i.e., loss of discoid form, dynamic filopodia formation [6] . This phenomenon is significantly increased in stenosed arteries in vivo, consistent with the role of platelets in vascular disease [10] .…”
Section: Platelet Bioenergeticsmentioning
confidence: 99%
“…In reciprocity, through the effect of those large amounts of factors released from platelet microparticles and exosomes with antiapoptotic plus proliferation signals and angiogenic factors, platelets reinforce tumor growth [135] . These factors additionally inhibit the immune system function that prevents tumor establishment and growth [ 136 , 137 ], and induce phenotypic changes, via epithelial-mesenchymal transition, of the tumor cells, which acquire invasiveness and thus enhance their metastatic potential [134] .…”
Section: Main Textmentioning
confidence: 99%
“…In addition, the heterotypic aggregates facilitate tumor cell survival in circulation, tumor cell arrest at the endothelium, and extravasation [138] . Likewise, platelets can aggregate with inflammatory cells perhaps providing an immune-evasive advantage [136] .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation